Comparison of Average Daily Maximum Rainfall in 2012 – 2022 at Patrang Station and Sumbersari Station, Jember City - Ahmad Ifan Fanandri; Amri Gunasti (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
High rainfall variability in Jember Regency, East Java, hampers flood mitigation and water resource management due to limited rainfall stations, necessitating validation of CHIRPS satellite data. This study compares the maximum daily average rainfall of Patrang and Sumbersari Stations with CHIRPS data for the 2012-2022 period. Using a comparative quantitative approach, the population is annual time-series data from both stations and the CHIRPS grid, with a purposive sample of 11 complete data pairs. Instruments include BMKG and CHIRPS observation data, analyzed using the Shapiro-Wilk normality test, Levene Test, and Independent Samples T-Test in SPSS with α=0.05. The results show no significant difference (Sig. 2-tailed=0.308-0.412, p>0.05), normal distribution (p>0.05), homogeneous variance (p=0.981), and strong Pearson correlation (r=0.983), confirming the similarity of characteristics. The conclusion states that both stations have similar hydrological representations that can represent each other, while CHIRPS is a reliable alternative for data-poor areas.